The improvement of technical preparation of sprinters on the initial stage of sport training - Maleniuk T.V (Kharkov National Pedagogical University, 2010)
Directions of perfection of technical preparation of sprinters are examined on the initial stage of the sporting training. The basic elements of technique at run are certain 100 meters. The system of criteria of estimation of technical preparedness of sprinters is developed. The certain lacks of technical preparedness are exposed. The method of improvement of technical preparation is developed and its efficiency is tested. The system of criteria of estimation of technical preparedness of sprinters is developed. A general tendency is exposed to their finding on middle, above average and to high levels.